Uji Aktivitas Antioksidan dan Kandungan Fitokimia Daun Benalu (Loranthus ferrugineus Roxb.) yang Tumbuh pada Ketinggian Tempat dan Inang Berbeda : Activity Antioxidant Test and Phytochemical Content of Mistletoe Leaves (Loranthus ferrugineus Roxb.) Growing at Different Altitudes and Host Types - Iwit, Seswita; Ardi; Syarif, Auzar (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2024)
Restrictions on synthetic antioxidants in several countries have caused the global community to switch to using natural antioxidants. One source of natural antioxidants is mistletoe leaves (Loranthus ferrugineus Roxb.).The presence of mistletoe in a place and host is an important aspect to pay attention to to get the best antioxidants. This research aims to determine the effect of different altitudes and host types on the antioxidant activity and phytochemical content of mistletoe leaves. This research was structured in a split-plot design with 2 factors, namely altitude (lowland and medium land) and host types (avocado, lime, cocoa, and dogfruit). Antioxidant activity test using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method and phytochemical screening using reagents. Variables observed included extract yield percentage, antioxidant activity (IC50 value), and phytochemical screening. The results showed that altitude and host type significantly affected the antioxidant activity of mistletoe leaves. Mistletoe leaves in avocado hosts in the lowlands and medium land showed the best antioxidant activity, namely 155,94 Âµg/mL and 156,25 Âµg/mL in the weak antioxidant category, and the highest phytochemical content, namely flavonoids, alkaloids, tannins, saponins, and steroids.